The association of anemia with high-sensitive cardiac troponin and its influence on the ESC 0/1h and 0/3h algorithms to triage patients with suspected acute myocardial infarction. (25th November 2020) - Haller, P.M; Neumann, J.T; Soerensen, N.A; Gossling, A; Hartikainen, T.S; Lehmacher, J; Zeller, T; Blankenberg, S; Westermann, D
Abstract: Introduction: According to the 4th Universal Definition of Myocardial Infarction (UDMI), anemia may cause acute and chronic myocardial injury indicated by elevated high-sensitive troponin (hs-cTn) concentrations, with unknown influence on triaging patients with suspected acute myocardial infarction (AMI). Purpose: To investigate the influence of anemia on hs-cTnI and the diagnostic performance of the ESC 0/1 and 0/3 hour (h) algorithms. Methods: Patients with suspected AMI were prospectively enrolled and stratified based on the hemoglobin (Hb) concentration at admission (females <12 g/dl, males <13g/dl). Hs-cTnI was measured at presentation, 1 and 3h later. Three independent cardiologists adjudicated the final diagnoses according to the 4th UDMI. Patients with ST-elevation AMI were excluded. Our primary endpoints were the safety to rule-out (negative predictive value [NPV]) and the efficacy to rule-in (positive predictive value [PPV]) AMI. Patients were followed for up to 4 years to assess all-cause mortality. Results: We included 2, 223 patients (64.1% males, age 65 [52; 75]) of whom 415 (18.7%) had anemia. The prevalence of AMI was numerically different for patients with and without anemia (16.4% and 12.9%, p=0.072). Hs-cTnI concentrations were significantly higher in patients with anemia and no AMI (p<0.001 for baseline, 1h and 3h, respectively), but not in patients with AMI (Fig, 1A). Sex- and age-adjusted linear regression modelling in patients without AMI revealed a significant association of Hb with hs-cTnI (Beta −0.10 [95% CI: −0.14, −0.06]; p<0.001; Fig. 1B). Safety and efficacy of both ESC algorithms were similar in patients with and without anemia; 0/1h (NPV 100.0% [95% CI: 94.7, 100.0]; PPV 52.7% [95% CI: 43.0, 62.3] vs. NPV 99.4% [95% CI: 98.5, 99.8]; PPV 55.7% [95% CI: 50.1, 61.1]); 0/3h (NPV 98.0% [95% CI: 95.3, 99.3]; PPV 48.4% [95% CI: 39.4, 57.5] vs. NPV 97.9 [95% CI: 97.0, 98.6], PPV 59.2 [95% CI: 53.7, 64.6]). During a median follow-up of 1.7 years and after stratification by either ESC algorithm, patients with compared to those without anemia experienced significantly worse outcome for all-cause death (p<0.001; Fig. 1C). In sex-, age- and baseline hs-cTnI-adjusted Cox-regression analysis, anemia was an independent predictor for all-cause death (adjusted hazard ratio [adjHR] 3.6 [95% CI: 2.6, 5.0]), cardiovascular death (adjHR 3.0 [95% CI: 1.8, 5.2]) and rehospitalization (adjHR 1.2 [95% CI: 1.0, 1.5], but not for incidental AMI (adjHR 2.0 [95% CI: 0.8, 4.9]) or revascularization (adjHR 0.8 [95% CI: 0.5, 1.3]). Conclusion: Despite the revealed association of Hb and hs-cTnI in the stable setting, the application of the ESC 0/1h and 0/3h algorithms in patients with suspected AMI and concomitant anemia is safe and provides similar efficacy. Patients with anemia experience considerable worse outcome and might therefore benefit from additional diagnostic measures and, potentially, treatment targeting anemia and its cause. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): German Center of Cardiovascular Research (DZHK) and an unrestricted grant by Abbott Diagnostics, Prevencio and Singulex.